The Effectiveness of Calcaneal Drilling for Treatment of Resistance Cases of Plantar Heel Pain - Al-Edanni, Mohammed SH. (AL-Kindy College Medical Journal, 2019)
Background: Plantar heel pain is a clinical syndrome characterized by pain and tenderness beneath the heel which is typically worse in the morning and improves after the first few steps in the day. It is a common and frequently disabling clinical complaint that may be caused by a broad spectrum of osseous or soft tissue disorders. Objective: To evaluate the effectiveness of an operation of multiple drilling of calcaneum for resistant plantar heel pain syndrome. Methods: During the period from November 2012 to August 2016, 17 patients (17heels) were enrolled in a cohort clinical study at the orthopedic unit in AL-Sheikh Zayed and Al-Wassity Hospitals. Result: Drilling of the calcaneum is a simple procedure achieving 70.6% cure in resistant ases with few complications provided good patient selection was done. Conclusion: Abnormalities in the intraosseous pressure within the calcaneum are a possible cause of plantar heel pain in some patients who failed to respond to conservative treatment